Muscle damage during a soccer World Cup preparatory and competition period - Bok, D.; Jukic, I. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To report creatine kinase ([CK]) responses during a soccer World Cup preparatory and first-leg period and to determine the influence of aerobic fitness on postmatch [CK] responses. Methods: Eleven national-team players were analyzed in this study. A lactate threshold test was performed during the first 3 d, whereas fingertip blood was drawn most mornings (21 out of 30 d) for [CK] measurements. One-way repeated-measures analysis of variance was used for determining the effect of time on [CK] measurements, whereas Pearson correlation coefficient was used for assessing associations between the changes in [CK] and velocities associated with blood lactate concentrations of 2 (v2) and 4 mmol/L (v4). Results: Peak [CK] concentrations were consistently reached on the first day after the match with values of 474 (261), 520 (419), and 460 (126) U/L but with no significant differences between them. [CK] concentrations returned to prematch values (331 [201] U/L) on the second day after the match. The change in [CK] concentration between prematch and postmatch day was largely correlated (r=.614, P=.044) with v2. Conclusions: Top-level soccer players display low levels of muscle damage during official tournaments, and they recover before the next match. Postmatch muscle damage is greater in players with higher aerobic endurance because this fitness quality enables them to execute high-intensity activities known to be a major contributor to muscle damage.